Eksplorasi Bibliometrik tentang Perkembangan Kajian Manuskrip dan Perpustakaan di Scopus - Mufidah, Imroatul; Putri, Desiana Ekasari; Sasmita, Amira Oribia Wanda; Joko Susilo (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2024)
This research aims to explore and analyze bibliometrics related to the development of manuscript and library studies in the Scopus database, related to the origin of the institutions with the most writing, the countries of origin with the most citations, annual scientific production, average citations per year and the topics most cited. often discussed. The research method used in this research is descriptive quantitative. Meanwhile, the database used in this research is Scopus and uses the R-Bibliometric Package (Biblioshiny) application to carry out data mapping and analysis. Data for 580 articles was downloaded from Scopus using the keywords